A holistic assessment of the sources, prevalence, and distribution of bisphenol A and analogues in water, sediments, biota and plastic litter of the Ebro Delta (Spain). (1st December 2022) - Gil-Solsona, R.; Castaño-Ortiz, J.M.; Muñoz-Mas, R.; Insa, S.; Farré, M.; Ospina-Alvarez, N.; Santos, L.H.M.L.M.; García-Pimentel, M.; Barceló, D.; Rodríguez-Mozaz, S.
Abstract: Bisphenol A (BPA) is one of the main ubiquitous compounds released from plastics in the environment. This compound, considered an endocrine disruptor, poses a risk to aquatic wildlife and human population, being included in multiple environmental monitoring programmes. Following the regulations restricting BPA use in the last years, BPA-like chemicals have been produced and used as BPA substitutes. However, they are not commonly included in monitoring programs yet and their presence is thus misrepresented, despite showing similar endocrine disrupting potential. In this work, an analytical method for analysing bisphenol A and five of its analogues (Bisphenol S, B, F, AF and Tetrabromobisphenol A) is described, validated for water (riverine, sea and wastewater), sediment, and biota (fish and biofilm) and applied to monitor their presence in the Ebro River Delta (NE Spain). In addition, plastic litter was also collected to evaluate their role as potential source of bisphenols. All compounds except BPF were detected in the analysed samples. Wastewater treatment plants (WWTPs) were discarded as major sources of BPs into the natural aquatic environment, as no BPs were detected in treated effluents. Indeed, the high levels of BPs in the natural environment could be related with direct discharge of raw wastewater from small rural population nucleus. The analysis of riverine plastic leachates yielded 4 out of the 6 BPs analysed, strengthening the hypothesis that plastic debris are also a source of BPs in the natural environment. Whereas Bisphenol S and BPA were detected in water and, to a limited extent, in biota, less polar analogues (mainly BPAF and TBBPA) were not found in any of the water samples. Instead, these hydrophobic BPs were found in fish tissues and biofilm, pointing out plastics and microplastics as their possible vectors. Finally, biofilm demonstrated its potential as sentinel of chemical contamination in freshwater environment. Graphical abstract: Image 1 Highlights: Bisphenols were studied in biotic and non-biotic fluvial compartments. Polar bisphenols detected in all environmental compartments. Less polar bisphenol analogues only found in fish tissues and fluvial biofilm. Plastic litter pointed out as a source of bisphenol contamination in river. Fluvial biofilm as a sentinel for bisphenols monitoring in the aquatic environment.